Three functional facets of calbindin D-28k - Schmidt, Hartmut (Frontiers in Molecular Neuroscience, 2012)
Many neurons of the vertebrate central nervous system (CNS) express the Ca2+ binding protein calbindin D-28k (CB), including important projection neurons like cerebellar Purkinje cells but also neocortical interneurons. CB has moderate cytoplasmic mobility and comprises at least four EF-hands that function in Ca2+ binding with rapid to intermediate kinetics and affinity. Classically it was viewed as a pure Ca2+ buffer important for neuronal survival. This view was extended by showing that CB is a critical determinant in the control of synaptic Ca2+ dynamics, presumably with strong impact on plasticity and information processing. Already 30 years ago, in vitro studies suggested that CB could have an additional Ca2+ sensor function, like its prominent acquaintance calmodulin (CaM). More recent work substantiated this hypothesis, revealing direct CB interactions with several target proteins. Different from a classical sensor, however, CB appears to interact with its targets both, in its Ca2+-loaded and Ca2+-free forms. Finally, CB has been shown to be involved in buffered transport of Ca2+, in neurons but also in kidney. Thus, CB serves a threefold function as buffer, transporter and likely as a non-canonical sensor.